Transformation of Licensing Services as Efforts to Increase Regional Income - Ratih Nur Aini (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
One of the agendas for transforming public services in Indonesia is to transform licensing services. The licensing service transformation in Jakarta Special Region Province is carried out by transforming the licensing service provider organization, i.e. the One-Stop Integrated Services and Investment Agency of Jakarta Special Region Province. This research is qualitative research with a descriptive approach and aims to explore or describe how the licensing service transformation is carried out and how it impacts on the regional income of Jakarta Special Region Province. The results of the study found that the One-Stop Integrated Services and Investment Agency transformed by changing the organizational structure, people, and the use of technology. The transformation carried out by DPMPTSP of Jakarta Special Region Province is proven to be able to increase the realization of investment achievement and the realization of regional levies revenue that comes from certain licensing fees.